Massive Open Online Courses and intercultural competence: analysis of courses fostering soft skills through language learning - Rai, Laxmisha; Deng, Chunrao; Lin, Shuyang; Fan, Liu (Frontiers in Psychology, 2023)
This paper aims to survey language teaching MOOCs that promote intercultural competence (IC). Specifically, the survey aims to identify the keywords most relevant to MOOCs with IC components, the languages taught, the offering countries, and the embedded soft skills. The selection of keywords is important because they can indicate connection between different disciplines. After trialing a broader set of keywords in several rounds of initial search, we identified five keywords that are the most relevant to language education with IC components on MOOCs: culture, intercultural, cross culture, multi culture, and society. Then courses with these five keywords on language learning are selected for further analysis. The results are summarized as follows: (1) Most language teaching MOOCs are found under the keyword “culture” , indicating a strong connection between language education and intercultural communication; (2) In terms of the target languages and the offering countries, it is found that English, Chinese, and Spanish are the major languages widely taught in the context of intercultural competence; China, USA, and Ireland are the three countries which offer the highest numbers of MOOCs in this respect; USA, UK, and Australia are the three countries which offer the highest numbers of MOOCs of different languages. The results indicate that a limited number of languages and offering countries dominate the language learning MOOCs. The study calls for a plurality of languages and cultures to be taught through MOOCs, making more diversified knowledge systems accessible to global audiences. (3) The language teaching MOOCs not only focus on language but also aim to foster five types of soft skills (language learning skills, communication skills, business and entrepreneurship skills, career development skills, and cultural development skills), suggesting that intercultural competence and its related soft skills are usually important components embedded in such MOOCs courses.